Data Journalism Projects Based on User-Generated Content. How La Nacion Data Transforms Active Audience into Staff - Palomo-Torres, María Bella; Teruel-Rodríguez, Laura; Blanco-Castilla, Elena Pilar (Taylor & Francis, 2019)
This article aims to contribute to the debate on audience participation in the media from three points of view: (1) demonstrating how data journalism enables an effective participation by the public in news production, (2) establishing a typology of the forms of contribution, and (3) performing an in-depth study of La Naci on (Argentina), as an example of success in collaborative data projects carried out in Latin America. In order to achieve these objectives, firstly, all the Global Editors Network Data Journalism Awards were analysed with the purpose of detecting projects involving user-generated content. Secondly, La Naci on was studied from an ethnographic perspective, as it is the medium with the most prizes in which citizen participation was detected. The results show that collaboration between media and audience can make large-scale journalism projects a reality, and also that citizens in Argentina are recruited by LN Data specially to boost political accountability.
Keywords: Sistemas de información - Análisis; Active audience; collaborative journalism; data journalism; open data; participation; reciprocal journalism; user generated content